Age, frequency, and iconicity in early sign language acquisition: Evid ence from the Israeli Sign Language MacArthur–Bates Communicative Deve lopmental Inventory - Novogrodsky, Rama; Meir, Natalia (Applied Psycholinguistics, 2020)
The current study described the development of the MacArthur–Bates Com municative Developmental Inventory (CDI) for Israeli Sign Language (IS L) and investigated the effects of age, sign iconicity, and sign frequ ency on lexical acquisition of bimodal-bilingual toddlers acquiring IS L. Previous findings bring inconclusive evidence on the role of sign i conicity (the relationship between form and meaning) and sign frequenc y (how often a word/sign is used in the language) on the acquisition o f signs. The ISL-CDI consisted of 563 video clips. Iconicity ratings f rom 41 sign-naïve Hebrew-speaking adults (Study 1A) and sign frequency ratings from 19 native ISL adult signers (Study 1B) were collected. I SL vocabulary was evaluated in 34 toddlers, native signers (Study 2). Results indicated significant effects of age, strong correlations betw een parental ISL ratings and ISL size even when age was controlled for , and strong correlations between naturalistic data and ISL-CDI scores , supporting the validity of the ISL-CDI. Moreover, the results reveal ed effects of iconicity, frequency, and interactions between age and t he iconicity and frequency factors, suggesting that both iconicity and frequency are modulated by age. The findings contribute to the field of sign language acquisition and to our understanding of potential fac tors affecting human language acquisition beyond language modality.
Keywords: Björn-2026-02-22; Sign language; acquisition; frequency; iconicity; vocabulary